Devotions : the selected poems of Mary Oliver - Oliver, Mary, 1935-2019 (2017)
"Throughout her celebrated career, Mary Oliver has touched countless readers with her brilliantly crafted verse, expounding on her love for the physical world and the powerful bonds between all living things. Identified as "far and away, this country's best selling poet" by Dwight Garner, she now returns with a stunning and definitive collection of her writing from the last fifty years. Carefully curated, these 200 plus poems feature Oliver's work from her very first book of poetry, No Voyage and Other Poems, published in 1963 at the age of 28, through her most recent collection, Felicity, published in 2015."--
From three rivers poetry journal and "three poems for James Wright" -- At Blackwater Pond -- The rabbit -- Three poems for James Wright -- From twelve moons -- Sleeping in the forest -- Snakes in winter -- Music lessons -- Entering the kingdom -- The night traveler -- Beaver moon-the suicide of a friend -- Last days -- The black snake -- The Truro bear -- Mussels -- Snow moon-black bear gives birth -- Strawberry moon -- Pink moon-the pond -- Aunt leaf -- Farm country -- The lamps -- From the river Styx, Ohio -- Learning about the Indians -- Going to Walden -- Night flight -- From no voyage and other poems -- No voyage -- Jack -- Beyond the snow belt -- The swimming lesson -- On winter's margin -- The return -- Morning in a new land
Includes index of titles and first lines
Keywords: Poetry; Poetry; Poetry; Poetry